Symbolic violence in nursing higher education: A narrative review - Pérez-Saavedra, Ana Patricia; Ayala-Zuluaga, Jose Enver; Mondragón-Sanchéz, Edna Johana (Universidad y Salud, 2025)
Introduction: Symbolic violence is one of the most common forms of interaction within society, imperceptible and naturalized, and it is also present in the academic field. Objective: To explore the existing literature towards the presence of symbolic violence in university pedagogical practices in nursing programs. Materials and methods: Narrative literature review between 2018 and 2024, using Scopus, Redalyc, Dialnet, Web of Science, Science Direct, DOAJ, and university repositories, through the methodology proposed by Arksey and O'Malley. Results: 24 articles were obtained for thematic analysis. The main subjects of study were found to be students; however, interactions between teachers and administrators are also protagonists. The use of qualitative methodologies is the most common, allowing for an understanding of the subjective dimension of symbolic violence. There is limited production related to pedagogical practices in nursing programs. Conclusions: The narrative suggest that scientific production towards the topic is increasing, violence based on gender has been the most analyzed topic in the academic context. It was found that there exist violent teaching practices in the classrooms, and that educational polices and institutional structures tend to generate discrimination and exclusion of some groups.